Population, Poverty, and Climate Change - Das Gupta, Monica (Oxford University Press on behalf of the World Bank, 2015)
This literature review focuses on the relationships between population, poverty, and climate change. Developed countries are largely responsible for global warming, but the brunt of the fallout will be borne by developing countries in forms such as lower agricultural output, poorer health, and more frequent natural disasters. Although carbon emissions per capita have leveled off in developed countries, they are projected to rise rapidly in developing countries because of economic growth and population growth. Unfortunately, the latter will rise most notably in the poorest countries, combining with climate change to slow poverty reduction. These countries have many incentives to lower fertility. Previous studies indicate that in high fertility settings, fertility decline facilitates economic growth and poverty reduction. It also reduces the pressure on livelihoods and frees resources that can be used to cope with climate change. Moreover, slowing population growth helps avert some of the projected global warming, which will benefit the poorest countries far more than it will benefit developed countries that lie at higher latitudes and/or have more resources to cope with climate change. Natural experiments indicate that family-planning programs are effective and highly pro-poor in their impact. While the rest of the world wrestles with the complexities of reducing emissions, the poorest countries will benefit from simple programs to lower fertility.